A Chest‐Laminated Ultrathin and Stretchable E‐Tattoo for the Measurement of Electrocardiogram, Seismocardiogram, and Cardiac Time Intervals. Issue 14 (21st May 2019) - Ha, Taewoo; Tran, Jason; Liu, Siyi; Jang, Hongwoo; Jeong, Hyoyoung; Mitbander, Ruchika; Huh, Heeyong; Qiu, Yitao; Duong, Jason; Wang, Rebecca L.; Wang, Pulin; Tandon, Animesh; et al.
Abstract: Seismocardiography (SCG) is a measure of chest vibration associated with heartbeats. While skin soft electronic tattoos (e‐tattoos) have been widely reported for electrocardiogram (ECG) sensing, wearable SCG sensors are still based on either rigid accelerometers or non‐stretchable piezoelectric membranes. This work reports an ultrathin and stretchable SCG sensing e‐tattoo based on the filamentary serpentine mesh of 28‐µm‐thick piezoelectric polymer, polyvinylidene fluoride (PVDF). 3D digital image correlation (DIC) is used to map chest vibration to identify the best location to mount the e‐tattoo and to investigate the effects of substrate stiffness. As piezoelectric sensors easily suffer from motion artifacts, motion artifacts are effectively reduced by performing subtraction between a pair of identical SCG tattoos placed adjacent to each other. Integrating the soft SCG sensor with a pair of soft gold electrodes on a single e‐tattoo platform forms a soft electro‐mechano‐acoustic cardiovascular (EMAC) sensing tattoo, which can perform synchronous ECG and SCG measurements and extract various cardiac time intervals including systolic time interval (STI). Using the EMAC tattoo, strong correlations between STI and the systolic/diastolic blood pressures, are found, which may provide a simple way to estimate blood pressure continuously and noninvasively using one chest‐mounted e‐tattoo. Abstract : A hair thin, skin soft, and highly stretchable e‐tattoo is created for high fidelity electro‐mechanoacoustic cardiovascular monitoring, made of Au electrodes and polyvinylidene fluoride vibration sensors. Such synchronous measurement affords the extraction of many characteristic cardiac time intervals among which the systolic time interval is found to have a strong negative correlation with blood pressure.